English phonology and pronunciation teaching - Rogerson-Revell, Pamela (London : Bloomsbury, 2011)
Covers key aspects of English phonology to help readers go on to teach pronunciation, diagnose problem areas and prioritize important skills. This book aims to provide a clear description of key aspects of English phonology in order to help teachers diagnose and prioritize problem areas in pronunciation.
Includes index.
Keywords: English language -- Phonology; English language -- Phonetics; English language -- Pronunciation